2023
DOI: 10.1186/s12978-023-01597-w
|View full text |Cite
|
Sign up to set email alerts
|

Women’s and health providers’ perceptions of companionship during labor and childbirth: a formative study for the implementation of WHO companionship model in Burkina Faso

Abstract: Introduction A key component of achieving respectful maternal and newborn care is labor companionship. Despite important health benefits for the woman and baby, there are critical gaps in implementing labor companionship for all women globally. The paper aims to present the perceptions and experiences of pregnant women, postpartum women, and health care providers regarding companionship during labor and childbirth, and to identify barriers and facilitating factors to the implementation of labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Others like Ethiopia have a low labour companionship, which was found to be 14.6% [ 23 ]. In a recent study in Burkina Faso, where 77 women, companions, and health workers were interviewed about their beliefs, opinions, and policies about labour companions, they found that hospitals were not allowing companions during labour and birth [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others like Ethiopia have a low labour companionship, which was found to be 14.6% [ 23 ]. In a recent study in Burkina Faso, where 77 women, companions, and health workers were interviewed about their beliefs, opinions, and policies about labour companions, they found that hospitals were not allowing companions during labour and birth [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study conducted by Bocoum and colleagues, the current function of a companion is to connect the birthing woman with healthcare professionals [14]. Moreover, mothers perceived a lack of companionship as a cause of loneliness and isolation [20]. Additionally, authors demonstrated that many participants experienced depression due to giving birth alone [21].…”
Section: Discussionmentioning
confidence: 99%
“…Women endorsed the importance of research about women's and communities' views on AVB, reflecting the relevant role of societal influence on birth preferences. 41 , 42 , 43 Participants emphasised the need to study what is the current knowledge of women and communities in LMICs about mode of birth in general and about AVB, as well as their attitudes towards both, since these are the starting point for change. Women underscored the importance of identifying the most efficient ways to inform women in contemporary societies, including through the use of mass and social media channels.…”
Section: Discussionmentioning
confidence: 99%